2017
DOI: 10.17345/rio18.29-55
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an accounting videogame in terms of attributes, motivation and learning outcomes

Abstract: Effectiveness of an accounting videogame in terms of attributes, motivation and learning outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…games on students motivation, the results of this study are consistent with those ofBuckley and Doyle (2014);Calabor et al (2015), andCarenys et al (2017).The results of this paper have several practical implications. First, the process explained in this study is useful for the accounting lecturers and other interested individuals who intend to develop a new game/ simulation or integrate games into their classroom routines.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…games on students motivation, the results of this study are consistent with those ofBuckley and Doyle (2014);Calabor et al (2015), andCarenys et al (2017).The results of this paper have several practical implications. First, the process explained in this study is useful for the accounting lecturers and other interested individuals who intend to develop a new game/ simulation or integrate games into their classroom routines.…”
supporting
confidence: 87%
“…They suggested that games have elements and attributes that improve learners' intrinsic and extrinsic motivation. Carenys et al (2017) investigated the sophomore students' perception of the effect of a video game about working capital using a researcher-made questionnaire. Students perceived the game experience to be motivating and conducive to their learning.…”
Section: Introductionmentioning
confidence: 99%
“…Successful teamwork is the result of mutual knowledge sharing and strong commitment between team members. Fostering collaboration and teamwork generates a high satisfaction with expertise and an intense achievement sentiment ( Carenys et al, 2017 ). The following hypothesis is treated:…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…Kaynak: Carenys, J., Moya, S. & Vila, M. (2017). Effectiveness of an accounting videogame in terms of attributes, motivation and learning outcomes.…”
Section: şEkil 2: Marty Raygun'un Bir Avuç Dolusu Doları (Marty Raygun's Fistful Of Dollars) Oyunu Ekran Görüntüsümentioning
confidence: 99%